Deletion of MicroRNA-21 Impairs Neovascularization Following Limb Ischemia: From Bedside to Bench - Chang, Wei-Ting; Lin, Yu-Wen; Huang, Po-Sen; Lin, You-Cheng; Tseng, Shih-Ya; Chao, Ting-Hsing; Chen, Zhih-Cherng; Shih, Jhih-Yuan; Hong, Chon-Seng (Frontiers in Cardiovascular Medicine, 2022)
With an increasing prevalence, peripheral arterial disease (PAD), cause by atherosclerosis is a new threat to public health beyond coronary artery disease and involves aberrant vascular endothelial cell proliferation and angiogenesis. The degree of vascular remodeling is influenced by the processes described. MicroRNA-21 (miR-21) has been found to play a critical role in cellular functions, including angiogenesis. Nevertheless, the effect of miR-21 on endothelial cells in response to hypoxia is largely unknown. Using wild-type C57BL/6J and miR-21-/- mice, we compared the capability of angiogenesis in response to hindlimb hypoxic/ischemia. In an in vitro study, we further studied whether overexpression of miR-21 mitigates hypoxia-induced apoptosis and impaired angiogenesis. Also, we prospectively collected the sera of patients with limb ischemia and followed the clinical information, including major adverse limb events (MALEs). Using laser Doppler perfusion imaging and CD31 staining, compared with miR-21-/- mice, wild-type mice expressed a significantly higher capability of angiogenesis and less apoptosis following 28 days of hindlimb hypoxic/ischemic surgery. In our in vitro study, after 24 hours of hypoxia, proliferation, migration, and tube formation were significantly impaired in cells treated with the miR-21 inhibitor but rescued by the miR-21 mimic. Mechanistically, by suppressing PTEN/ PI3K/AKT, miR-21 promoted angiogenesis and suppressed apoptosis in endothelial cells post hypoxia. In patients with limb ischemia, the high expression of circulating miR-21 was associated with less subsequent MALE. Collectively, miR-21 could be a biomarker associated with the endogenous ability of angiogenesis and reflect subsequent MALE in patients. Additionally, abolishing miR-21 impairs angiogenesis and promotes apoptosis post limb ischemia. Further studies are required to elucidate the clinical applications of miR-21.